2007
DOI: 10.1677/joe-07-0436
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of stem cell-like progenitor cells in human adult pancreas

Abstract: The origin of cells replacing ageing b-cells in adult life is unknown. This study assessed the expression of classic stem cell markers: Oct4, Sox2 and CD34 in islet-enriched fractions versus exocrine cell-enriched fractions from 25 adult human pancreases following human islet isolation. Expression of Oct4, Sox2 and CD34 mRNAs was found in all cell samples, with no significant differences between endocrine and exocrine cell fractions. Immunohistochemical staining for Oct4, Sox2, CD133, CD34, CK19, insulin and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
3
31
0
1
Order By: Relevance
“…Cells expressing OCT4 termed 'very small embryonic-like stem cells' have recently been isolated from murine pancreas (Zuba-Surma et al 2009), and it has been proposed that these may provide a quiescent pool of stem cells for replenishing tissue-specific progenitors in times of extensive tissue injury. The presence of cells expressing OCT4 and SOX2 in unmanipulated human pancreas has previously been reported (Zhao et al 2007). In this study, we have confirmed the size of OCT4-positive cells as only w1 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Cells expressing OCT4 termed 'very small embryonic-like stem cells' have recently been isolated from murine pancreas (Zuba-Surma et al 2009), and it has been proposed that these may provide a quiescent pool of stem cells for replenishing tissue-specific progenitors in times of extensive tissue injury. The presence of cells expressing OCT4 and SOX2 in unmanipulated human pancreas has previously been reported (Zhao et al 2007). In this study, we have confirmed the size of OCT4-positive cells as only w1 .…”
Section: Discussionsupporting
confidence: 87%
“…In established adults (Manesso et al 2009) and in response to injury (Dor et al 2004, Xu et al 2008, however, the potential for non-b-cell sources including facultative endocrine progenitor cells has been proposed in convincing studies. Several groups have identified and isolated putative stem cells from adult pancreas (Seaberg et al 2004, Suzuki et al 2004, Eberhardt et al 2006, but the expression of the pluripotency-associated embryonic stem (ES) cell markers has only been reported in exploratory studies on mice (Zuba-Surma et al 2009) and unmanipulated human pancreas (Zhao et al 2007, Al-Turaifi et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the generation of β cells from undifferentiated or partially differentiated precursors, may also be involved in the maintenance of β cell mass . Very little is known about these putative stem cells, which may reside within the islet itself (Zulewski et al 2001;Petropavlovskaia & Rosenberg 2002)or in the pancreatic ducts (Bonner-Weir et al 2000;Zhao et al 2007). The convincing data demonstrating that β cells maintain their mass through the replication of preexisting β cells (Dor et al 2004;Teta et al 2007) has questioned the need for islet progenitor cells under normal physiological conditions .…”
Section: Survival and Regeneration Of β Cellsmentioning
confidence: 99%
“…Several studies have reported that progenitors reside within the pancreas itself. Possible sources of these progenitors are the pancreatic ductal epithelium, [4][5][6][7][8][9][10][11] acinar tissue, [12][13][14] islets 15,16 and mesenchyme. [17][18][19][20][21][22][23] Studies have indicated that mesenchymal stem cells (MSCs) are multipotent and capable of deriving functional endoderm.…”
mentioning
confidence: 99%